Environmental Factors Modulate the Role of orf21 Sigma Factor in Clavulanic Acid Production in Streptomyces Clavuligerus ATCC27064 (2022)
Sigma factors and sigma factor-related mechanisms control antibiotic production in Strep- tomyces. In this contribution, the orf21 gene was overexpressed in the wild-type strain of Strepto-myces clavuligerus ATCC2764, yielding S. clavuligerus/pIORF21, to further evaluate its regulatory effect on clavulanic acid (CA) biosynthesis under different culture medium conditions. The orf21 overexpression, regulated under the constitutive promoter ermE*, led to 2.6-fold increase in CA production in GSPG medium, and a 1.8-fold decrease using ISP medium. As for GYM and MYM media, S. clavuligerus/pIORF21 strain showed higher aerial mycelium production compared to control. Glycerol uptake rate profile was affected by orf21 overexpression. Furthermore, in GSPG, S. clavuligerus/pIORF21 slightly increased the expression of adpA and gcas genes, whilst, in ISP, the claR gene expression was drastically reduced, which is consistent with a decreased CA production, observed in this medium. These findings suggest the protein encoded by the orf21 gene plays a role in the regulation of CA biosynthesis as a response to the nutritional composition of the medium.